Finite element analysis of the reinforcement ratio effect on tension stiffening in FRP reinforced concrete beams. (15th October 2022) - Chen, Guoxiong; An, Ru; Xu, Jianfei; Fu, Shihua
Highlights: A tension stiffening model was proposed by introducing a correction factor. Loading curves were reproduced for FRP RC beams with various reinforcement ratios. Cracking patterns from FE analysis were well consistent with those from experiment. Uneven strain of FRP bars was discussed related with non-uniformity coefficient. Relationship of correction factor -reinforcement ratio was proposed and verified. Abstract: Fiber reinforced polymer (FRP) has been used as an alternative to steel in some appropriate conditions. In this study, a model was developed for prediction of tension stiffening in FRP RC beams with various reinforcement ratios by introducing a coefficient, named correction factor. By using an inverse approach to obtain the optimal correction factor, the results of finite element analysis were consistent with the experimental results in both load-midspan displacement curves and cracking patterns. Uneven distributions in the strain of FRP bars were also observed. A relationship between the correction factor and the reinforcement ratio was proposed by fitting and verified by additional simulations that were in agreement with the corresponding experiments. It indicates that the proposed model is suitable for predicting the behavior of FRP RC beams with various reinforcement ratios.